SUBJECT OLYMPIADS AS ONE THE FORMS OF STUDENTS’ SELF-STUDY AT THE DEPARTMENT OF THERAPEUTIC DENTISTRY OF HSEE OF UKRAINE "UMSA" - T.O. Petrushanko; N.M. Ilenko (Український стоматологічний альманах, 2018)
Self-work is one of the most important components of the educational process which provides the integration of various types of individual and collective study activities during classroom and extracurricular activities. In the context of the modern education system, self-work dominates among other types of student`s education after practical training of students and allows to consider the accumulation of knowledge as an object of the student's own activity. At the Department of Therapeutic Dentistry one of the forms of initiated independent work of students is a subject Olympiad. Dental Olympiad gives opportunity to expand the medical horizon, to show erudition, non-traditional thinking, to arouse interest in scientific activity. The article is devoted to the organization and holding of the subject Olympiad in the Department of Therapeutic Dentistry with students of the dental faculty. The advantages and disadvantages of this type of educational activity in the preparation of competitive specialists were analysed in the transition from the initial to the higher levels of independence of mastering the future profession.